1969
DOI: 10.12669/pjms.321.8841
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and practices of physicians’ towards evidence-based medicine and physicians perceived barriers in Jeddah, Saudi Arabia

Abstract: Objective:To investigate physicians’ perceptions and practices towards Evidence-Based Medicine (EBM) and physicians perceived barriers in one institute of Saudi Arabia.Methods:One hundred seventeen practicing physicians at King Abdulaziz University Hospital, Jeddah were included in the study. A validated questionnaire was used for collecting data. The questionnaire had four parts and included questions addressing perceptions and practices about EBM as well as associated variables and barriers to practicing it.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
7
16
0
Order By: Relevance
“…Similar findings were found with family physicians in Kuwait [ 23 ], who frequently relied on their own judgements (68.6%) and medical books (52.8%) to make clinical decisions. These findings are supported by the results reported by other regional studies conducted in Saudi Arabia and Qatar [ 29 ]. Furthermore, previous studies regarding EBM in pharmacy practice have shown that in Jordan [ 7 ], pharmacists relied mostly on their own judgements in giving pharmaceutical information (80%), in addition to medical representatives’ information (72%) and medical textbooks (54.5%), rather than EBM processes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar findings were found with family physicians in Kuwait [ 23 ], who frequently relied on their own judgements (68.6%) and medical books (52.8%) to make clinical decisions. These findings are supported by the results reported by other regional studies conducted in Saudi Arabia and Qatar [ 29 ]. Furthermore, previous studies regarding EBM in pharmacy practice have shown that in Jordan [ 7 ], pharmacists relied mostly on their own judgements in giving pharmaceutical information (80%), in addition to medical representatives’ information (72%) and medical textbooks (54.5%), rather than EBM processes.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in the interviews, the unavailability of supportive resources for practising EBM was mentioned as the main barrier, besides the lack of higher management support for a formal decision to incorporate EBM into practice, in which all barriers would be eliminated accordingly. Similar barriers were found in many other professions, including medicine [ 29 ], nursing [ 5 ] and physical therapy [ 30 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…al, and in Saudi Arabia by Baig et. al, found that while clinicians have a very positive attitude towards EBM, they also have low proficiency to apply elements of EBM to patient care 14,15 . Al Wahaibi conducted a study in Oman that cited many clinicians who felt that barriers to practicing EBM existed, such as access to evidence resources or time constraints that prevent them from fully applying EBM in clinical practice 16 .…”
Section: Introductionmentioning
confidence: 99%
“…al, and in Saudi Arabia by Baig et. al, found that while clinicians have a very positive attitude towards EBM, they have low pro ciency to apply elements of EBM to patient care 15,16 . Al Wahaibi conducted a study in Oman where many clinicians indicated they felt that many barriers to practicing EBM existed, such as access to evidence resources or time constraints that prevent them from fully applying EBM in clinical practice 17 .…”
Section: Introductionmentioning
confidence: 99%